2021
DOI: 10.3390/molecules26206301
|View full text |Cite
|
Sign up to set email alerts
|

Monascin and Ankaflavin of Monascus purpureus Prevent Alcoholic Liver Disease through Regulating AMPK-Mediated Lipid Metabolism and Enhancing Both Anti-Inflammatory and Anti-Oxidative Systems

Abstract: Alcohol metabolism causes an excessive accumulation of liver lipids and inflammation, resulting in liver damage. The yellow pigments monascin (MS) and ankaflavin (AK) of Monascus purpureus-fermented rice were proven to regulate ethanol-induced damage in HepG2 cells, but the complete anti-inflammatory and anti-fatty liver mechanisms in the animal model are still unclear. This study explored the roles of MS and AK in improving alcoholic liver injury. MS and AK were simultaneously fed to evaluate their effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In addition, AMPK is an energy sensor that is an upstream molecule of autophagy (W. S. He, Wu, Ren, Yu, & Zhao, 2021). In the former publications, Monascin regulated AMPK-mediated ethanol-induced liver injury by regulating p62 and autophagy crosstalk with the Keap1 / Nrf2 pathway (Lai, Hsu, Pan, & Lee, 2021). Similarly, in our study, an increase of p-AMPK protein expression was observed by pretreatment with PCP, and then promoting p62-mediated autophagic degradation of Keap1.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, AMPK is an energy sensor that is an upstream molecule of autophagy (W. S. He, Wu, Ren, Yu, & Zhao, 2021). In the former publications, Monascin regulated AMPK-mediated ethanol-induced liver injury by regulating p62 and autophagy crosstalk with the Keap1 / Nrf2 pathway (Lai, Hsu, Pan, & Lee, 2021). Similarly, in our study, an increase of p-AMPK protein expression was observed by pretreatment with PCP, and then promoting p62-mediated autophagic degradation of Keap1.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have confirmed and proved that ABL can reduce the inflammatory response induced by LPS by blocking the nuclear translocation of NF-κB p65 and inhibiting the phosphorylation and degradation of IκBα . Some data also suggest that alcohol exposure promotes the release of cytokines IL-1β and TNF-α . Therefore, it reduces alcohol-induced liver toxicity by preventing the production of IL-1β and TNF-α.…”
Section: Discussionmentioning
confidence: 88%
“… 36 Some data also suggest that alcohol exposure promotes the release of cytokines IL-1β and TNF-α. 37 Therefore, it reduces alcohol-induced liver toxicity by preventing the production of IL-1β and TNF-α. In our study, ABL significantly inhibited the increase of IL-1β and TNF-α caused by alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, MPs are red (RMPs, such as monascorubramine and rubropunctamine), orange (OMPs, such as rubropunctatin and monascorubrin), and yellow (YMPs, such as monascin and ankaflavin; Kim and Ku, 2018 ; Liu et al, 2019a ). It has been reported that YMPs are an excellent colorants and are safe, with anti-inflammatory, anti-fatty, antitumor, and antioxidant functions ( Wu et al, 2021 ; Huang et al, 2021b ), improving alcoholic liver injury and preventing lipid accumulation ( Zhou et al, 2019 ; Lai et al, 2021 ), with great prospects for use in food and pharmaceutical industries. However, YMPs are normally hydrophobic or alcohol-soluble intracellular pigments in submerged fermentation, increasing the cost of separation and purification, and limiting their application ( Gong and Wu, 2016 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%